A Study On Training Needs Analysis [TNA] Process Among Manufacturing Companies Registered With Pembangunan Sumber Manusia Berhad [PSMB] At Bayan Lepas Industrial Area. - Mohamad Yusof, Ahmad Nasir (2010)
This research was carried out with the purpose of understanding whether organization are adopting the recommended practices in TNA processes. Kajian ini dijalankan bertujuan untuk memahami serta menyelidiki sama ada organisasi mempraktikan cadangan pengkaji terdahulu dalam melaksanakan proses TNA.